Translation Analysis of Social Cultural Words in Bumi Manusia Movie - Arshila Andista Mantika; Nurochman (International Journal of English and Applied Linguistics (IJEAL), 2023)
Translation problems may arise because of cultural differences in movie subtitles. Thus, subtitling strategies have become important for translating social and cultural information. This study aims to identify the social cultural words using Newmarks’s (1988) theory and to investigate the subtitling strategies employed by the translators using Pedersen’s (2011) theory. The data used in this research are cultural words in Indonesian subtitles and English subtitles in the movie Bumi Manusia. Moreover, the researcher used the descriptive qualitative method. As a result, the researcher found that there were 166 social culture words found in the movie, which were work, name, terms of address, kinship, and leisure terms. The result revealed that the most frequent cultural-related terms of the social cultural words are names of a person with 34% of data. Furthermore, this study found that the translator employed seven subtitling strategies when translating cultural words, which were official equivalent (39%), retention (37%), substitution (14%), direct translation (4%), generalization (4%), omission (2%), and specification (1%). It can be concluded that the official equivalent is the dominant strategy applied by the translator, followed by retention.